Characteristics and key limitations of traditional methods for accounting hunting animals and digital technologies for solving the existing problems (review) - A. Yu. Prosekov (Аграрная наука Евро-Северо-Востока, 2020)
In order to solve the set of acute problems and for transition to sustainable development of hunting economy of Russia it is necessary to increase the accuracy and objectivity of data on number of hunting animals. Existing methods of accounting are based on direct recounting or analysis of certain indirect evidence of their vital activity, and are mainly developed during the Soviet period of development of hunting science, i.e. are irrelevant. In this research, a descriptive analysis of existing (traditional) methods of accounting for hunting animals (aviation, ground accounting) was carried out. The results of the study have revealed the main advantages and limitations of traditional methods. Restrictions are most often associated with both "human factor"and theoretically and methodologically outdated databases. In order to eliminate existing shortcomings, fundamental innovations in the accounting of hunting animals are necessary. In current conditions, these are primarily digital technologies. The review deals with digital modifications to the main accounting methods, including the use of GPS systems, the use of camera traps and the equipping of aircraft with cameras. The method of improving standard air accounting has become one of the most demanded digital methods of accounting for hunting animals. Thus, the expensive traditional aviation has been replaced by unmanned aerial vehicles (aircraft-type drones, quadrocopters), which have lower flight costs and lack shortcomings of standard aircraft accounting (restriction of human eye viewing, unsuitable weather conditions, biological features of animals, etc.). These new improved methods allow to study hunting grounds and obtain reliable information on the state of forest resources.